(untitled) (Journal of Engineering, 2005)
Cracks may appear in structures due to manufacturing processes and some time are appeared in the structure product from casting, these struetures may be used but in the life less than the design life according to crack propagation on it. In this research a thick cylinder has one crack or more is investigated to estimate the life under pulsation internal pressure. Finite element method with J-integral approach has been used to evaluate the numerical strain energy release rate (J) for the thick cylinder and the stress intensity factor (SIF J-integral method is most accurate method to evaluate the SIF for the elastic-plastic materiel by considering the local plastic zone near crack tip. Software developed using the FEM; J-integral; SIF and Paris formula to estimate the life of the component is presented with many working examples.